Critical behavior of spinel MnV2O4 investigated by dc-magnetization - Zhang, Lei; Han, Hui; Qu, Zhe; Fan, Jiyu; Ling, Langsheng; Zhang, Changjin; Pi, Li; Zhang, Yuheng (Journal of applied physics, 2014)
Critical behavior of spinel vanadate oxide MnV2O4 has been investigated by the dc-magnetization study. Critical exponents β = 0.349 ± 0.009, γ = 0.909 ± 0.002, and δ = 2.913 ± 0.003 are obtained in the critical asymptotic region around the critical temperature TC. With these critical exponents, experimental M–T–H curves collapse onto two independent universal branches below and above TC, respectively, indicating the reliability of the obtained results. The critical exponents γ and δ are close to the mean-field model with long-range interaction, while the value of β deviates to the 3D-Heisenberg model with short-range coupling. It is suggested that a long-range ferromagnetic coupling exists for Mn2+-Mn2+ interaction, which competes with the short-range interaction of V3+ sublattice. Moreover, the precursor phenomenon of the orbital ordering could be observed from the critical behavior, which indicates orbital fluctuation in MnV2O4.